The optimal design of structures using ACO and EFG. (October 2016) - Shobeiri, Vahid
Abstract This paper presents an ant colony optimization (ACO) algorithm incorporating the element free Galerkin (EFG) method for topology optimization of continuum structures. The EFG method is used to derive shape functions using the moving least squares approximation. The essential boundary conditions are enforced by the Lagrange multiplier method. Several numerical examples are presented to show the validity and feasibly of the proposed method. The common numerical instabilities of the ACO algorithm do not exist in the results.